Factors Predictive of 90-Day Morbidity, Readmission, and Costs in Patients Undergoing Pelvic Exenteration. Issue 5 (June 2018) - Bogani, Giorgio; Signorelli, Mauro; Ditto, Antonino; Martinelli, Fabio; Casarin, Jvan; Mosca, Lavinia; Leone Roberti Maggiore, Umberto; Chiappa, Valentina; Lorusso, Domenica; Raspagliesi, Francesco
Abstract : Objective: Pelvic exenteration for recurrent gynecological malignancies is characterized by a high rate of severe complications. Factors predictive of morbidity, readmission, and cost were analyzed. Methods: Data of consecutive patients undergoing pelvic exenteration between January 2007 and December 2016 were prospectively evaluated. Results: Fifty-eight patients were included in the analysis. Anterior, posterior, and total exenterations were executed in 39 (67%), 9 (16%), and 10 (17%) patients, respectively. Ten (15.5%) severe complications occurred: 8 (20.5%), 0 (0%), and 1 (10%) after anterior, posterior, and total exenterations, respectively. Radiotherapy dosage, time between radiotherapy and surgery, and previous administration of chemotherapy did not influence 90-day complications and readmission. At multivariable analysis, albumin levels less than 3.5 g/dL (odds ratio, 16.2 [95% confidence interval, 2.85–92.8]; P = 0.002) and history of deep vein thrombosis (odds ratio, 9.6 [95% confidence interval, 0.93–98.2]; P = 0.057) were associated with 90-day morbidity. Low albumin levels independently correlated with readmission ( P = 0.011). The occurrence of 90-day postoperative complications and readmission increased costs of a median of +12, 500 and +6000 euros, respectively ( P < 0.05). Conclusions: Preoperative patient selection is a key point for the reduction of postoperative complications after pelvic exenteration. Further prospective studies are warranted to improve patient selection.